Nitrate fate in coastal unconfined aquifers influenced by preferential flows - Gao, Chao; Kong, Jun; Wang, Jun; Chen, Weilun (Frontiers in Marine Science, 2024)
This study examined the influence of preferential flow on pore water flows and marine nitrogen transport reaction in variable saturation and variable density coastal aquifers. The 2-D unconfined aquifer model established was based on the software COMSOL by coupling the dynamic and chemical processes together. The results showed that preferential flow affects groundwater flow and salinity distribution, leading to a more complicated mixing process. The preferential flow resulted in an increase in mixing zone area and the upper saline plume area of 10.33 and 2.62 m2, respectively, a decrease in saltwater wedge area of 7.22 m2, and an increase in nitrate (NO3-) removal efficiency from 7.9% to 8.97%. The NO3- removal efficiency increases progressively with the depth (h) and quantity (n) of preferential flows; however, it decreases after a certain quantity. Further quantitative analysis revealed an increase in the intensity of nitrification and dissolved oxygen inflow flux with preferential flow depth and quantity increase. This phenomenon usually occurs on coasts where biological caves are abundant. The results also offer significant implications for designing engineering measures to mitigate saltwater intrusion and are significant to prevent groundwater quality deterioration in coastal zones.